The influence of welding condition on the microstructure of WC hardfacing coating on carbon steel substrate - Nagentrau, M.; Mohd Tobi, A.L.; Sambu, M.; Jamian, S. (Elsevier, 2019)
Tungsten carbide (WC) hardfacing coating technique is widely used to improve the performance of carbon steel blade exposed to acidic and abrasive conditions during production. This paper deals with the influence of welding parameters on the microstructure and carbide distribution of WC. WC hardfacing was deposited onto carbon steel by shielded metal arc welding (SMAW). Welding parameters such as welding current, number of weld layers, electrode drying and base material preheat were the focus of this work. Coating hardness, microstructure and elemental composition were analysed in detail. The effects of the welding parameters on WC hardfacing coating microstructure and hardness value were characterized by scanning electron microscope (SEM) and micro-Vickers hardness tester respectively. The larger carbide growth in overall coating region is mainly dictated by high current (200 A), increased number of weld layers (3 layers) and presence of base material preheat due to sufficient heat energy initiating carbide growth. The investigation also revealed that high current affected the growth of smaller carbide particles in matrix region significantly. Meanwhile, number of weld layers and base material preheat influences were seen during hardfacing with lower welding current. The absence of electrode drying led to uniform smaller carbide distribution in matrix region. It was found that increased number of large carbides and uniformly distributed smaller carbides in WC hardfacing deposit increased the hardness value of the coating.